Family communication about fertility preservation in adolescent males newly diagnosed with cancer. Issue 7 (25th February 2021) - Olsavsky, Anna L.; Theroux, Charleen I.; Dattilo, Taylor M.; Klosky, James L.; O'Brien, Sarah H.; Quinn, Gwendolyn P.; Gerhardt, Cynthia A.; Nahata, Leena
Abstract: Background: Approximately half of male childhood cancer survivors experience fertility impairment, which can cause psychological distress. Sperm banking remains underutilized among adolescent males with cancer. Parent recommendation influences banking decisions, yet multi‐informant studies have not been conducted to examine fertility preservation (FP) communication and decision making in this population. This study explored FP communication among mothers, fathers, and their male adolescents newly diagnosed with cancer. Procedure: Thirty‐three male adolescents, 32 mothers, and 22 fathers completed semi‐structured interviews 1–2 months after cancer diagnosis addressing this question: Tell me more about conversations you had about fertility preservation/sperm banking with your health care providers, parents/son, other family members, or anyone else . Interviews were audio‐recorded and transcribed verbatim for thematic content analysis. Results: Five process themes emerged: (1) reliance on health care team and social support networks to facilitate FP decisions (only parents); (2) withholding parental opinion and deferring the decision to the adolescent; (3) ease of communication (primarily adolescents); (4) communication barriers/facilitators; (5) not being present or not remembering details of FP conversations with health care providers (primarily fathers and adolescents). Four content themes included: (1) preference for biological (grand)parenthood; (2) consideration of adolescent's future partner's desire for biological parenthood (primarily parents); (3) banking while it is a viable option; (4) openness to alternative parenthood options (e.g., adoption/fostering, primary parents). Conclusions: Understanding variation in what family members discuss and consider relevant when making FP decisions is an important step toward improving pediatric oncofertility care. Interventions are needed to facilitate family FP‐related conversations and optimize decisional satisfaction over time.